Association of quality of life, anxiety, and depression with restless leg syndrome in the hemodialysis patients - Mahjabeen Yaseen; Furqan Ahmad Jarullah; Sadia Yaqoob; Hassan Abdullah Shakeel; Hamza Maqsood; Sadiq Naveed (BMC Research Notes, 2021)
Abstract Objectives Restless Legs Syndrome (RLS) is commonly known to cause morbidity in patients on hemodialysis, making them prone to chronic mental health illnesses such as depression and anxiety, and also adversely impact quality of life. In this study, we examined the association of quality of life, anxiety, and depression with restless leg syndrome in the hemodialysis patients at Karachi Institute of Kidney Diseases. Results About 26.7% of the participants reported RLS among the sample size Presence of RLS was not associated with quality of life, depression, and anxiety. However, p-values < 0.05 were significant for body-mass index (BMI), diabetes mellitus as a cause of end-stage renal disease, and serum albumin levels. Majority (82.5%) of the RLS-diagnosed patients had moderate to severe symptoms with 16 (40%) and 17 (42.5%) clients, respectively.